Ideas about globalization in Sociološki pregled/ Sociological review: The possibility of applying David Held et al's division into three schools of thought - Popić, Snežana S. (Sociološki pregled, 2018)
Humankind has gone through several stages of growth of global awareness, which can be divided depending on the historical manifestation of the intensity of globalization in the main areas of society. Te scientifc interest in globalization has lasted for several decades, and it is expressed through diﬀerent theoretical perspectives on globalization. Although it has become commonplace in many theoretical models to divide the set of ideas about globalization into skepticism and hyperglobalism, more rarely transformationalism, the question of whether the list of main arguments in works of such authors complies with D. Held’s division remains open. In order to describe the conceptual diversity of globalization in Serbia, the frst part of this paper presents an analysis of ideas about globalization from the journal ’Sociološki pregled/ Sociological Review’, while the second part considers data on the possibility of applying David Held et. al’s division into three schools of thought about globalization: skeptics, hyperglobalizers and transformationalists. In accordance with the set of objectives of the research, this paper applies the method of content analysis, whereby the data coding model is constructed in a deductive strategy. Tis paper concludes that only a few of the criteria of this division are relevant for distinguishing the ideas of globalization in the domestic sociological feld.
Keywords: globalization; ideas; journal; Sociološki pregled/Sociological Review; David Held et. al’s division of three schools of thought about globalization; method of content analysis